Gramme: Game your grammar/ Nurul Shatirah Zainol and Rafidah Abd Karim - Zainol, Nurul Shatirah; Abd Karim, Rafidah (2023)
As the world continues to develop, the mastery of the global language among every individual should be the utmost priority aimed by the government. To aim for the bigger purpose, one should start by taking a small step. Hence, to achieve the aim of national excellence of English language mastery, this effort should be first implemented and amplified at the lower level, specifically within the primary education level. Grammar is one of the most crucial and core elements that indicates one’s fluency in English language. GRAMME! (Grammar and Game!) is a programme that is aimed at primary students with emphasis on the English language grammar learning and practice. This is a game-based programme that introduces the English grammar learning and practice through various online gameplays. The flexible, fun, and interactive learning methods offered by GRAMME! is hoped to facilitate educators especially in the teaching and learning process of the primary students. The conventional and traditional methods of English grammar teaching can also be changed through GRAMME! as this programme guarantees more students’ involvements, and a two-way teaching and learning process.